Epstein-Barr virus, the germinal centre and the development of Hodgkin's lymphoma - Mohamed, Ghada; Vrzalikova, Katerina; Cader, Fathima Zumla; Vockerodt, Martina; Nagy, Eszter; Flodr, Patrik; Yap, Lee-Fah; Diepstra, Arjan; Kluin, Philip M; Rosati, Stefano; Murray, Paul (The Journal of general virology, 2014)
The relationship between Epstein-Barr virus (EBV) and the germinal centre (GC) of the asymptomatic host remains an enigma. The occasional appearance of EBV-positive germinal centres in some patients, particularly those with a history of immunosuppression, suggests that EBV numbers in the GC are subject to immune control. The relationship, if any, between lymphoid hyperplasia with EBV-positive germinal centres and subsequent or concurrent lymphomagenesis remains to be clarified. As far as the development of EBV-associated Hodgkin's lymphoma is concerned, the suppression of virus replication, mediated by LMP1 on the one hand, and the loss of B-cell receptor signalling on the other, appears to be an important pathogenic mechanism. A further important emerging concept is that alterations in the microenvironment of the EBV-infected B-cell may be important for lymphomagenesis.
Keywords: Cell Differentiation; Middle Aged; mužské pohlaví; Adult; mladý dospělý; Hodgkin Disease; replikace viru; B-lymfocyty; Young Adult; ženské pohlaví; virus Epsteinův-Barrové; proteiny virové matrix; B-Lymphocytes; Humans; Viral Matrix Proteins; receptory antigenů B-buněk; Herpesvirus 4, Human; Pseudolymphoma; lidé středního věku; Epstein-Barr Virus Infections; infekce virem Epsteina-Barrové; Hodgkinova nemoc; Receptors, Antigen, B-Cell; buněčná diferenciace; dospělí; pseudolymfom; Female; Virus Replication; Germinal Center; zárodečné centrum lymfatické uzliny; lidé; Male